(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Background: Ayurveda is a highly evolved and codified system of life and health science based on its own unique and original fundamental concepts and principles. One of them is the Paradi Gunas (properties). Paradi Gunas (properties) are ten in number and have a wide application aiming at the success of treatment in which, choice of medicine and dietary rules play vital role. For success in the treatment understanding the role and action of a medicine is important, and this can be achieved by the use of Paradi Gunas (properties). Objective: To apply the concept of Paradi Gunas (properties) on Aarogyavardhini Rasa, a ployherbo-mineral medicine during different stages of processing. Data Source: This literary review has used the data source from various online portals as well as books in Ayurveda. Conclusion: The use of Paradi Gunas was studied on the pre-processing, processing and the therapeutic stages of Aarogyavardhini Rasa and its applications were noted. This can be a primary step towards deeper understanding of its role in therapeutics.